The BiteBarrier perimeter: A passive spatial device for tick control and bite prevention - Maria V. Murgia; Laurie Widder; Catherine A. Hill (Current Research in Parasitology and Vector-Borne Diseases)
Tick-borne diseases (TBDs) impact human and animal health on a global scale. Prevention of TBDs relies primarily on prevention of tick bites. New bite-prevention technologies are needed as an alternative to current approaches such as topical repellents and treated clothing which suffer low user compliance. To date, no passive spatial devices have been commercialized for area protection against ticks. The BiteBarrier (formerly the Personal Insect Repellent Kit, PIRK), a passive, lightweight device that emits transfluthrin, offers to fill this gap. In a previous study, we demonstrated contact toxicity of the BiteBarrier substrate to three tick species, Ixodes scapularis, Dermacentor variabilis and Amblyomma americanum, and reported differences in efficacy depending on species and short-range spatial efficacy against I. scapularis adult females. Here, we extended analyses and demonstrated modest spatial activity of the BiteBarrier substrate against A. americanum and D. variabilis adult females. Using a dual-choice behavioral assay, we showed that the three tick species preferred an area of untreated substrate. Lastly, we present a novel perimeter assay, developed to assess the efficacy of the BiteBarrier ground-based prototype against ticks. At short-range in a Peet Grady-style chamber, the BiteBarrier perimeter induced greater than 90% knockdown of I. scapularis adult females at 1 and 2 h post-exposure and 90% mortality at 48 h post-exposure. Taken together, study findings indicate the potential of the BiteBarrier perimeter to control ticks at near range and potentially, to protect against tick bites.